Evaluating the effect of a campus-wide social norms marketing intervention on alcohol-use perceptions, consumption, and blackouts. Issue 3 (3rd April 2018) - Su, Jinni; Hancock, Linda; Wattenmaker McGann, Amanda; Alshagra, Mariam; Ericson, Rhianna; Niazi, Zackaria; Dick, Danielle M.; Adkins, Amy
ABSTRACT: Objective : To evaluate the effect of a campus-wide social norms marketing intervention on alcohol-use perceptions, consumption, and blackouts at a large, urban, public university.Participants : 4, 172 college students (1, 208 freshmen, 1, 159 sophomores, 953 juniors, and 852 seniors) who completed surveys in Spring 2015 for the Spit for Science Study, a longitudinal study of students' substance use and emotional health.Methods : Participants were e-mailed an online survey that queried campaign readership, perception of peer alcohol use, alcohol consumption, frequency of consumption, and frequency of blackouts. Associations between variables were evaluated using path analysis.Results : We found that campaign readership was associated with more accurate perceptions of peer alcohol use, which, in turn, was associated with self-reported lower number of drinks per sitting and experiencing fewer blackouts.Conclusions : This evaluation supports the use of social norms marketing as a population-level intervention to correct alcohol-use misperceptions and reduce blackouts.